Highly Stretchable and Air-Stable PEDOT:PSS/Ionic Liquid Composites for Efficient Organic Thermoelectrics - Kee, Seyoung; Kim, Hyunho; Neophytou, Marios; Emwas, Abdul Hamid; Baran, Derya; Paleti, Sri Harish Kumar; El Labban, Abdulrahman; Alshareef, Husam N. (My University, 2019)
Thermoelectric (TE) generators that are capable of providing sustainable energy conversion under dynamic mechanical stresses have been explored for realizing autonomous wearable electronics. However, finding extremely deformable, efficient, and air-stable TE materials is still a major challenge. Here, we report highly stretchable and efficient organic TE materials from aqueous composites of poly(3,4-ethylenedioxythiophene):poly(4-styrenesulfonate) (PEDOT:PSS) and ionic liquids (ILs). In this composite, ILs simultaneously enhance the Seebeck coefficient and electrical conductivity of PEDOT:PSS (up to 35 μV K -1 and 538 S cm -1 , respectively) by controlling its oxidation level and nanostructure. Moreover, the resulting fibrous structure with IL-assisted soft domains leads to outstanding mechanical deformability and durability, enabling that the PEDOT:PSS/IL films simply coated on elastomeric substrates maintain the TE functionality under tensile strain (ϵ) up to 70% and repetitive stretching cycles with 30% ϵ without severe degradation in TE performance. Furthermore, we also demonstrate the long-term TE stability of PEDOT:PSS/IL composites maintaining >80% of the initial performance after 10 days under ambient conditions. Our finding proves the potential of this novel composite as a stretchable and air-stable organic TE material.
Keywords: Deformation; Ionic liquids; Tensile strain; Thermoelectric energy conversion